2007
DOI: 10.1073/pnas.0700609104
|View full text |Cite
|
Sign up to set email alerts
|

Global and regional drivers of accelerating CO 2 emissions

Abstract: carbon intensity of economy ͉ carbon intensity of energy ͉ emissions scenarios ͉ fossil fuels ͉ Kaya identity

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

16
953
1
8

Year Published

2010
2010
2016
2016

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 1,527 publications
(978 citation statements)
references
References 9 publications
16
953
1
8
Order By: Relevance
“…1); the A2 scenario is a scenario that is based on assumptions of a very heterogeneous world economy with high population growth, moderate overall economic growth, and resulting emissions that accelerate throughout the 21st Century. Notably, until recently, the A2 scenario was viewed as a reasonable "worst case" scenario, but recent evaluations have shown that, in the past decade, emissions have actually exceeded the A2 trajectory (Raupauch et al 2007). Consequently, A2 is now viewed as more of a middle-of-the-road scenario (compared, e.g., to A1Fi in Fig.…”
Section: Projectionsmentioning
confidence: 99%
“…1); the A2 scenario is a scenario that is based on assumptions of a very heterogeneous world economy with high population growth, moderate overall economic growth, and resulting emissions that accelerate throughout the 21st Century. Notably, until recently, the A2 scenario was viewed as a reasonable "worst case" scenario, but recent evaluations have shown that, in the past decade, emissions have actually exceeded the A2 trajectory (Raupauch et al 2007). Consequently, A2 is now viewed as more of a middle-of-the-road scenario (compared, e.g., to A1Fi in Fig.…”
Section: Projectionsmentioning
confidence: 99%
“…1), but the large population and high speed of economic development have been primary drivers of the recent acceleration in global carbon emissions [12]. China's economic growth is projected to continue at higher than 7% per year; at this rate, GDP would quadruple in 20 years [13].…”
Section: Global Warmingmentioning
confidence: 99%
“…Moreover, the CO 2 emissions increase (Raupach et al, 2007) is exceeding even the most pessimistic of the IPCC projections (IPCC, 2001). Therefore, humankind will be forced to apply geoengineering to counter the unwanted consequences of global warming.…”
Section: Introductionmentioning
confidence: 99%